SYSTEM THEORY BASED MULTIPLE BEAMFORMING - Trung, Nguyen Huu; Anh, Nguyen Thuy; Duc, Nguyen Minh; Binh, Doan Thanh; Tan, Le Trung (Vietnam Journal of Science and Technology, 2017)
In this paper, the problem of analysis and design of large-scale multiple beamforming system is considered by system theory approach. We consider the response of system parameters by set of objective functions in a critical condition, which is unable to access measurement data or the data size is large. The reduced-order model is built and the robust solution is found for a multiple beamforming system. The Monte Carlo simulation results show that the proposed multiple beamforming system yields significant performance against over existing methods.